1970
DOI: 10.1128/aem.19.2.287-289.1970
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Treponema pallidum from Tissue Debris Through Continuous-Particle Electrophoresis

Abstract: Treponema pallidum can only be cultured in living animal tissue, such as rabbit testes. However, the extract of these organisms from the testicular material leaves the T. pallidum contaminated with tissue debris. This paper describes the separation of T. pallidum from the debris by continuous-particle electrophoresis. The importance of equilibration time before electrophoresis is discussed. Treponema pallidum at present can be propagated only in living animal tissues. Large numbers of T. pailidum can be obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1971
1971
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…
A molecular characterization of cross-reactive antigens of Treponema pallidum Nichols and Treponema phagedenis biotype Reiter that are reactive with normal and syphilitic human sera is described. At least 8 common polypeptides, 14 T. pallidum-specific antigens, and 2 T. phagedenis biotype Reiter-specific antigens were identified.Antigenic characterization of Treponema pallidum has been hampered by the inability to obtain large quantities of pure, motile, and virulent organisms (1,9,10,21,22,(28)(29)(30). Nonpathogenic treponemes, however, can be grown in vitro in pure culture.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
A molecular characterization of cross-reactive antigens of Treponema pallidum Nichols and Treponema phagedenis biotype Reiter that are reactive with normal and syphilitic human sera is described. At least 8 common polypeptides, 14 T. pallidum-specific antigens, and 2 T. phagedenis biotype Reiter-specific antigens were identified.Antigenic characterization of Treponema pallidum has been hampered by the inability to obtain large quantities of pure, motile, and virulent organisms (1,9,10,21,22,(28)(29)(30). Nonpathogenic treponemes, however, can be grown in vitro in pure culture.
…”
mentioning
confidence: 99%
“…Antigenic characterization of Treponema pallidum has been hampered by the inability to obtain large quantities of pure, motile, and virulent organisms (1,9,10,21,22,(28)(29)(30). Nonpathogenic treponemes, however, can be grown in vitro in pure culture.…”
mentioning
confidence: 99%
“…Chandler and Clark (2) filtered testicular extracts through membranes of graded porosity, but this failed to separate treponemes from tissue components. Schmale et al (9) recovered much cleaner preparations by continuous particle curtain electrophoresis. However, this procedure damaged the organisms in that it converted one-third to one-half of the spirochetes in the cleaner fractions to spherical forms (i.e., ballooning of the outer envelope) and diminished the immunofluorescent staining of the rest, suggesting that they had lost some cellular constituent.…”
mentioning
confidence: 99%
“…Although Hunter et al (7) standardized methodology for preparing FTA-absorbed (ABS) antigen that was free of rabbit globulin, sensitive techniques revealed that these T. pallidum preparations were still contaminated with rabbit testicular material (5). The development of the continuous particle electrophoresis method for separation of T. pallidum from testicular material (16) resulted in the availability of a purified antigen for use in the FTA-ABS test. This continuous particle electrophoresis antigen is no longer available, and its preparation was technically difficult and expensive.…”
mentioning
confidence: 99%